A Unique Variation of Azygos System of Veins - Badagabettu, Satheesha Nayak (J Cardiovasc Echogr, 2016)
Knowledge of variations of azygos and hemiazygos veins is of importance to cardiothoracic surgeons and radiologists during various surgical, radiological, and echography techniques. We report some unique variations of azygos system of veins observed during dissection classes for undergraduate medical students. The azygos vein was formed as usual by the union of right subcostal and ascending lumbar veins. The vein ascended upward and to the left to reach the midline at the level of the 9(th) thoracic vertebra. After ascending till 5(th) thoracic vertebra, it gradually inclined to the right of midline and terminated by opening into the superior vena cava at the level of the 3(rd) thoracic vertebra. There was no major variation in the tributaries of the azygos vein on the right side, except that the right superior intercostal vein crossed behind the azygos vein from right to left and opened into the left side of the azygos vein. Further, two anastomotic veins connected the 10(th), 11(th) and 12(th) posterior intercostal veins with each other to form two anastomotic circles on the right side of 10(th) to 12(th) thoracic vertebrae. The hemiazygos vein bifurcated on the left side of the 10(th) thoracic vertebra and the two ends opened into the azygos vein at the level of 9(th) and 10(th) thoracic vertebrae forming a venous circle in front of the 10(th) thoracic vertebra. The course of accessory hemiazygos vein was noteworthy. Instead of its classic descending course, the vein ascended upward from the left side of the 8(th) thoracic vertebra till the 6(th) thoracic vertebra before opening into the azygos vein.